Al-Si-Fe-Mg series high-thermal-conductivity aluminum alloy and preparation method and heat dissipation structure thereof
By adding specific elements to the aluminum alloy and performing die-casting and aging treatment, the contradiction between the mechanical properties and thermal conductivity of the aluminum alloy is solved, and the excellent integration of the mechanical properties, thermal conductivity and molding properties of the aluminum alloy is achieved.
Patent Information
- Application Number
- CN202510120875.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-02-05
AI Technical Summary
While improving the mechanical properties of existing aluminum alloys, it is difficult to maintain good thermal conductivity and molding properties.
The Al-Si-Fe-Mg-based high-thermal conductivity aluminum alloy is used to optimize the microstructure of the alloy by adding elements such as Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE and Ni, and performing die-casting and multi-stage aging treatment.
It achieves excellent integration of mechanical properties, thermal conductivity and molding properties of aluminum alloys, and improves the comprehensive performance of aluminum alloys.
Smart Images

Figure SMS_1
Abstract
Description
[0001] The present invention is a divisional application, the original application number is 202410168688.8, the application date is February 5, 2024, and the name is Al-Si-Fe-Mg series high thermal conductivity aluminum alloy and its preparation method and heat dissipation structure. Technical Field
[0002] The present invention relates to the technical field of aluminum alloys, and in particular to an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, a preparation method of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, and a heat dissipation structure. Background Art
[0003] Aluminum alloy has the advantages of low melting point, low cost, easy recycling, good thermal conductivity, and suitable for die casting. It is widely used in the preparation of structural parts for mobile phones and other products. In order to improve the mechanical properties of structural parts, other alloying elements must be added, and the addition of alloying elements will reduce the thermal conductivity of aluminum alloys. Therefore, how to coordinate the relationship between the mechanical properties and thermal conductivity of aluminum alloys and produce aluminum alloys with excellent mechanical properties, thermal conductivity and die casting properties is a technical problem that technicians in the field of high thermal conductivity aluminum alloy technology need to solve. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the present invention provides an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, aiming to obtain an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy with excellent thermal conductivity, mechanical properties and die-casting forming properties.
[0005] The present invention provides an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, which contains aluminum, 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.11-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, 0.001-0.05% Ni by mass, 0-0.1% Co by mass, and 0.1% Cu by mass. -0.01% Be, and 0.0001-0.1% RE by mass percentage, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy is subjected to die casting and aging treatment, the aging treatment includes primary low-temperature aging treatment, secondary low-temperature aging treatment, and tertiary high-temperature aging treatment, wherein the temperature of the primary low-temperature aging treatment is -100°C to -200°C, and the time is 1h to 15h; the temperature of the secondary low-temperature aging treatment is 0°C to 70°C, and the time is 1h to 24h; the temperature of the tertiary high-temperature aging treatment is 280°C to 350°C, and the time is 0.05h to 15h.
[0006] The present invention also provides a method for preparing an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, comprising the following steps: The aluminum source is subjected to a first heating treatment to obtain aluminum liquid; Adding Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni to the aluminum liquid, performing a second heating treatment, and obtaining an alloy liquid; Refining and slagging the alloy liquid, and testing its composition and content; and After the composition and content are tested to be qualified, the alloy liquid after the refining treatment and the slag removal treatment is subjected to die casting treatment and aging treatment to obtain an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, wherein the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.11-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, and 0.001-0.05% Zn by mass. The present invention relates to a nickel alloy having a Ni content of 0.001-0.05%, a Co content of 0-0.1% by mass, a Be content of 0-0.01% by mass, and a RE content of 0.0001-0.1% by mass, wherein the aging treatment comprises a primary low-temperature aging treatment, a secondary low-temperature aging treatment, and a tertiary high-temperature aging treatment, wherein the primary low-temperature aging treatment is performed at a temperature of -100°C to -200°C, and the time is 1h to 15h; the secondary low-temperature aging treatment is performed at a temperature of 0°C to 70°C, and the time is 1h to 24h; the tertiary high-temperature aging treatment is performed at a temperature of 280°C to 350°C, and the time is 0.05h to 15h.
[0007] The present invention also provides a heat dissipation structure, at least part of which is made of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy or the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy prepared by the preparation method of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy. DETAILED DESCRIPTION
[0008] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0009] An embodiment of the present invention provides an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, which contains aluminum, and further contains Si with a mass percentage content of 5-8%, Fe with a mass percentage content of 0.4-0.8%, Cu with a mass percentage content of 0.001-0.05%, Mg with a mass percentage content of 0.05-0.4%, Sr with a mass percentage content of 0.005-0.04%, Zn with a mass percentage content of 0.001-0.05%, Ni with a mass percentage content of 0.001-0.05%, Co with a mass percentage content of 0-0.1%, Be with a mass percentage content of 0-0.01%, and RE with a mass percentage content of 0.0001-0.1%, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%.
[0010] In a preferred embodiment, the Al-Si-Fe-Mg high thermal conductivity aluminum alloy contains 6-7.5% Si by mass, 0.5-0.7% Fe by mass, 0.005-0.04% Cu by mass, 0.1-0.3% Mg by mass, 0.01-0.03% Sr by mass, 0.002-0.01% Zn by mass, 0.001-0.009% Ni by mass, 0-0.05% Co by mass, and 0-0.005% Be by mass, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is 5.5-9%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.18-0.3%.
[0011] The sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, preferably not more than 8.5%, and further preferably not more than 8%. In this way, while ensuring the excellent mechanical properties and thermal conductivity of the aluminum alloy, it is avoided that too many elements are added to form a solid solution in the aluminum matrix. In one embodiment, the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is 5.5-9%, preferably 6-8.5%, and further preferably 6.5-7%, and specifically can be 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, or 9%. In one embodiment, the sum of the total content of elements other than Al in the aluminum alloy is 5.5-9%, preferably 6-8.5%, and further preferably 6.5-7%, and specifically can be 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, or 9%.
[0012] The sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%, preferably 0.1-0.5%, further preferably not more than 0.2-0.3%, and again preferably 0.18-0.3%, specifically 0.052%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, 0.42%, 0.44%, 0.46%, 0.48%, or 0.5%.
[0013] The sum of the mass percentage contents of Cu, Mg, Zn, and Ni is 0.057-0.55%, preferably 0.1-0.5%, and further preferably 0.2-0.4%. Specifically, it may be 0.057%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, 0.52%, 0.54%, or 0.55%.
[0014] The mass percentage content of Si may be 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, or 8%.
[0015] The mass percentage content of Fe may be 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.7%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, or 0.8%.
[0016] The mass percentage content of Cu can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.011%, 0.012%, 0.013%, 0.014%, 0.015%, 0.016%, 0.017%, 0.018%, 0.019%, 0.02%, 0.021%, 0.022%, 0.023%, 0.024%, 0.025%, 0.026%, 0.027%, 0.028%, 0.029%, 0.030%, 0.031%, 0.032%, 0.033%, 0.034%, 0.035%, 0.036%, 0.037%, 0.038%, 0.039%, 0.040%, 0.041%, 0.042%, 0.043%, 0.044%, 0.045%, 0.046%, 0.047%, 0.048%, 0.049%, 0.050%, 0.051%, 0.052%, 0.053%, 0.054%, 0.055%, 0.056%, 0.057%, 0.058%, 0.059%, 0.01 .025%, 0.026%, 0.027%, 0.028%, 0.029%, 0.03%, 0.031%, 0.032%, 0.033%, 0.034%, 0.035%, 0.036%, 0.037%, 0.038%, 0.039%, 0.04%, 0.041%, 0.042%, 0.043%, 0.044%, 0.045%, 0.046%, 0.047%, 0.048%, 0.049%, or 0.05%.
[0017] The mass percentage content of Mg is 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39% or 0.4%.
[0018] The mass percentage content of Sr may be 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.011%, 0.012%, 0.013%, 0.014%, 0.015%, 0.016%, 0.017%, 0.018%, 0.019%, 0.02%, 0.021%, 0.022%, 0.023%, 0.024%, 0.025%, 0.026%, 0.027%, 0.028%, 0.029%, 0.03%, 0.031%, 0.032%, 0.033%, 0.034%, 0.035%, 0.036%, 0.037%, 0.038%, 0.039%, or 0.04%.
[0019] The mass percentage content of Zn can be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.011%, 0.012%, 0.013%, 0.014%, 0.015%, 0.016%, 0.017%, 0.018%, 0.019%, 0.02%, 0.021%, 0.022%, 0.023%, 0.024%, 0.025%, 0.026%, 0.027%, 0.028%, 0.029%, 0.030%, 0.031%, 0.032%, 0.033%, 0.034%, 0.035%, 0.036%, 0.037%, 0.038%, 0.039%, 0.040%, 0.041%, 0.042%, 0.043%, 0.044%, 0.045%, 0.046%, 0.047%, 0.048%, 0.049%, 0.050%, 0.051%, 0.052%, 0.053%, 0.054%, 0.055%, 0.056%, 0.057%, 0.058%, 0.059%, 0.01 .025%, 0.026%, 0.027%, 0.028%, 0.029%, 0.03%, 0.031%, 0.032%, 0.033%, 0.034%, 0.035%, 0.036%, 0.037%, 0.038%, 0.039%, 0.04%, 0.041%, 0.042%, 0.043%, 0.044%, 0.045%, 0.046%, 0.047%, 0.048%, 0.049%, or 0.05%.
[0020] The mass percentage content of Ni may be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.012%, 0.014%, 0.016%, 0.018%, 0.02%, 0.022%, 0.024%, 0.026%, 0.028%, 0.03%, 0.032%, 0.034%, 0.036%, 0.038%, 0.04%, 0.042%, 0.044%, 0.046%, 0.048%, or 0.05%.
[0021] The mass percentage content of Be may be 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, or 0.01%.
[0022] The mass percentage content of Co may be 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%.
[0023] The mass percentage content of RE may be 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.011%, 0.012%, 0.013%, 0.014%, 0.015%, 0.016%, 0.017%, 0.018%, 0.019%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%.
[0024] RE is at least one of La, Ce, Pr, Nd, Er, Sm, Y, and Gd.
[0025] The mass ratio of Mg to Cu is 1-50:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties of the aluminum alloy gradually increase. The mass ratio of Mg to Cu is preferably 5-40:1, more preferably 10-30:1, and further preferably 15-20:1, and specifically can be 1:1, 2:1, 4:1, 6:1, 7:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, or 50:1.
[0026] The mass ratio of Mg, Cu, and Zn is 5-500:0.1-20:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties of the aluminum alloy gradually increase. The mass ratio of Mg, Cu, and Zn is preferably 10-400:0.5-15:1, more preferably 10-200:1-10:1, and further preferably 20-50:2-5:1. Specifically, it can be 5:0.1:1, 5:1:1, 5:5:1, 5:10:1, 5:20:1, 10:0.1:1, 10:1:1, 10:5:1, 10:10:1, 1 0:20:1, 100:0.1:1, 100:1:1, 100:5:1, 100:10:1, 100:20:1, 200:0.1:1, 200:1:1, 200:5:1, 200:10:1, 200:20:1, 500:0.1:1, 500:1:1, 500:5:1, 500:10:1, or 500:20:1.
[0027] The mass ratio of Si to Fe is 5-20:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Si to Fe is preferably 10-20:1, and more preferably the mass ratio of Si to Fe is 15-20:1, specifically 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, or 20:1.
[0028] The mass ratio of Si to Sr is 200-1500:1. Within the range of this mass ratio, as the mass ratio decreases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Si to Sr is preferably 500-1000:1, more preferably 700-800:1, and specifically can be 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1, 1000:1, 1100:1, 1200:1, 1300:1, 1400:1, or 1500:1.
[0029] The mass ratio of Be, Co, and Fe is 0.001-0.03:0.004-0.25:1. Within this mass ratio range, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Be, Co, and Fe is preferably 0.005-0.02:0.005-0.2:1, more preferably 0.01-0.015:0.01-0.05:1, specifically 0.001:0.004:1, 0.001:0.01:1, 0.001:0.05:1, 0.001:0.1:1, 0.001:0.2:1, 0.001:0.25:1, 0.005:0.004:1, 0.005:0.01:1, 0.005:0.05:1, 0.005:0.1:1, 0.005:0.2:1, 0.005:0 .25:1, 0.01:0.004:1, 0.01:0.01:1, 0.01:0.05:1, 0.01:0.1:1, 0.01:0.2:1, 0.01:0.25:1, 0.02:0.004:1, 0.02:0.01:1, 0.02:0.05:1, 0.02:0.1:1, 0.02:0.2:1, 0.02:0.25:1, 0.03:0.004:1, 0.03:0.01:1, 0.03:0.05:1, 0.03:0.1:1, 0.03:0.2:1, or 0.03:0.25:1.
[0030] The mass ratio of Co, Ni, and Be is 0.1-100:0.4-50:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Co, Ni, and Be is preferably 1-50:1-30:1, and more preferably 5-20:1-15:1. Specifically, it can be 0.1:0.4:1, 0.1:1:1, 0.1:5:1, 0.1:10:1, 0.1:20:1, 0.1:30:1, 0.1:40:1, 0.1:50:1, 1:0.4:1, 1:1:1, 1:5:1, 1:10:1, 1:20:1, 1:30:1, 1:40:1, 1:50:1, 10:0.4:1, 10 :1:1, 10:5:1, 10:10:1, 10:20:1, 10:30:1, 10:40:1, 10:50:1, 50:0.4:1, 50:1:1, 50:5:1, 50:10:1, 50:20:1, 50:30:1, 50:40:1, 50:50:1, 100:0.4:1, 100:1:1, 100:5:1, 100:10:1, 100:20:1, 100:30:1, 100:40:1, or 100:50:1.
[0031] The mass ratio of Fe to Co is 1-250:1. Within this mass ratio range, as the mass ratio increases, the thermal conductivity of the aluminum alloy gradually increases. The mass ratio of Fe to Co is preferably 10-80:1, more preferably 30-50:1, and specifically can be 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1, 190:1, 200:1, 210:1, 220:1, 230:1, 240:1, or 250:1.
[0032] The mass percentage content of a single impurity in the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy is less than 0.02%, and the sum of the mass percentage content of the impurities is less than 0.1%. Mn, Ti, Cr, and V can be used as impurities, and the sum of their mass percentage content is not more than 0.03%, preferably not more than 0.025%, and more preferably not more than 0.02%.
[0033] The mass percentage content of Mn may be 0-0.009%, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, or 0.009%.
[0034] The mass percentage content of Ti, Cr and V can be 0-0.008%, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, or 0.008%.
[0035] In one embodiment, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 6-7.5% Si by mass, 0.5-0.7% Fe by mass, 0.005-0.04% Cu by mass, 0.1-0.3% Mg by mass, 0.01-0.03% Sr by mass, 0.002-0.01% Zn by mass, 0.001-0.01% Ni by mass, 0.005-0.05% Co by mass, and 0.00 1-0.005% Be, 0.0005-0.05% RE, 0.001-0.009% Mn, 0.001-0.008% Ti, 0.001-0.008% Cr, and 0.001-0.008% V, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is 5.5-9%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.18-0.3%.
[0036] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.05-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, 0.001-0.05% Ni by mass, 0-0.1% Co by mass, 0-0.01% Be by mass, and 0.0001-0.1% RE by mass, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%. Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni within the above content range interact with each other as a whole, ensuring that the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy has better formability and excellent mechanical properties and thermal conductivity. The details are as follows: (1) When the mass percentage content of Si is 5-8%, on the one hand, Si can improve the fluidity and density of aluminum alloy, thereby improving the forming performance and mechanical properties of aluminum alloy. On the other hand, Si can react with other elements as much as possible to form a second phase to avoid the adverse effect of Si dissolved in the aluminum matrix on the thermal conductivity of aluminum alloy. Specifically, Si can react with Al, Fe, Cu, Mg, Mn, etc. to form Mg2Si, AlFeSi, AlMnSi, AlFeSiCu, AlFeMgSi, AlFeMnSi and other second phases; (2) When the mass percentage of Fe is 0.4-0.8%, on the one hand, Fe can reduce the sticking tendency of aluminum alloy castings and improve the mechanical properties and thermal conductivity of aluminum alloys. On the other hand, Fe can react with other elements as much as possible to form a second phase to avoid the adverse effect of Fe dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Fe can react with Al, Si, Mg, Cu, Mn, Ni, etc. to form Al3Fe, AlFeSi, AlFeMgSi, AlFeSiCu, AlFeSiNi, AlFeMgSiNi, AlFeMnSi, FeNiAl9 and other second phases; (3) When the mass percentage of Cu is 0.001-0.05%, on the one hand, Cu can improve the mechanical properties, thermal conductivity, and fatigue resistance of aluminum alloys. On the other hand, Cu can react with other elements to form a second phase as much as possible to avoid the adverse effect of Cu dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Cu can react with Al, Fe, Si, Mg, Zn, etc. to form second phases such as CuAl2, AlFeSiCu, Al2CuZn, (CuMg)Al2, etc. In addition, Cu can also promote the precipitation of second phases such as Mg2Si, Mg2Zn, Mg2SiZn, (CuMg)Al2, AlFeMgSi, AlFeMgSiNi, etc., increase their volume fraction and dispersion, and reduce the solid solubility of the above elements in the aluminum matrix; (4) When the mass percentage content of Mg is 0.05-0.4%, on the one hand, Mg can improve the mechanical properties and thermal conductivity of aluminum alloys, and on the other hand, Mg can react with other elements to form a second phase as much as possible to avoid the adverse effect of Mg dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Specifically, Mg can react with Al, Fe, Si, Cu, Zn, Ni, etc. to form second phases such as Mg2Si, Mg2Zn, Mg2SiZn, (CuMg)Al2, AlFeMgSi, AlFeMgSiNi, etc. Mg can also promote the precipitation of second phases such as CuAl2, AlFeSiCu, Al2CuZn, (CuMg)Al2, etc., increase their volume fraction and dispersion degree to reduce the solid solubility of the above elements in the aluminum matrix; (5) When the mass percentage of Sr is 0.005-0.04%, on the one hand, Sr can be modified through the heterogeneous nucleation theory or twin valley mechanism to refine the second phase such as eutectic silicon, improve the thermal conductivity and mechanical properties of the aluminum alloy, and transform the β-AlFeSi phase in the ingot into the Chinese character α-AlFeSi phase to improve the mechanical properties of the aluminum alloy. On the other hand, Sr can preferentially combine with Fe, Cu, Mn, Cr, Si and other elements to form dispersion strengthening to avoid the adverse effect of Sr dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. In addition, Sr can also promote the precipitation of CuAl2, Mg2Si and other phases to reduce the solid solubility of these alloy elements in the aluminum matrix; (6) When the mass percentage of Zn is 0.001-0.05%, on the one hand, Zn can improve the mechanical properties of aluminum alloys, and on the other hand, Zn can react with other elements to form a second phase as much as possible to avoid the adverse effect of Zn dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Zn can react with Al, Mg, Cu and Si to form second phases such as MgZn2, Mg2SiZn, Al2CuZn, etc. Zn can eliminate elemental Si to reduce the adverse effect of elemental Si on the performance of aluminum alloys. Zn can also promote the precipitation of phases such as Mg2Si and Al2Cu, thereby improving mechanical properties and thermal conductivity. (7) When the mass percentage of Ni is 0.001-0.05%, on the one hand, Ni can be used to improve the mechanical properties and thermal conductivity of aluminum alloys. On the other hand, Ni can react with other elements to form a second phase as much as possible to avoid the adverse effect of Ni dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Specifically, Ni can react with Al, Fe, Mg, Si, etc. to form second phases such as Al3Ni, AlFeSiNi, AlFeMgSiNi, FeNiAl9, etc., to promote the precipitation of elements such as Cu, Mg, Zn, Si, Fe, etc. dissolved in the alloy; Ni can also refine grains, promote the precipitation of strengthening phases such as CuAl2, (CuMg)Al2, Mg2Si, increase the volume fraction and dispersion of the precipitated phase, and reduce the solid solubility of alloy elements in the aluminum matrix. In addition, Ni and Cu and Mg can promote each other's precipitation to improve the thermal conductivity and mechanical properties of aluminum alloys. (8) When the mass percentage of Co is not more than 0.1%, Co can refine the grains to improve the thermal conductivity and mechanical properties of aluminum alloys. On the other hand, it can also react with other elements to form a second phase as much as possible to avoid the adverse effect of Be dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Specifically, Co can react with Al, Fe, Si, etc. to form Al 15 (Fe, Co)3Si2, Al3(Fe, Co) and other second phases. In addition, Co has a refining effect on the Al3Fe phase, which can transform the coarse needle-shaped and flake-shaped β-Al3Fe phase into small flower-shaped and fine strip-shaped α-Al 15 (Fe,Co)3Si2 phase can also promote the α-Al 15 The precipitation of (Fe, Co)3Si2 phase further improves the mechanical properties and thermal conductivity of aluminum alloy. The composite addition of Ni and Co can effectively modify Fe and transform free Fe into the second phase. The composite addition of Co, Ni and Be can quickly reduce the solid solubility of each other in the alloy and increase the volume fraction of the second phase to improve the mechanical properties and thermal conductivity of aluminum alloy. (9) When the mass percentage content of Be is not more than 0.01%, Be can transform the eutectic Si phase from a lamellar phase to a fine phase to refine the Si phase, thereby reducing or eliminating the adverse effects of Si on the aluminum alloy. Be can also transform the plate-like β intermediate phase into a relatively harmless Chinese character-shaped Be-Fe (Al8Fe2SiBe) phase to reduce or eliminate the adverse effects of Fe on the performance of the aluminum alloy. It can also reduce the formation of Mg-containing Fe-rich phases, thereby increasing the Mg content in the aging process. On the other hand, Be can combine with vacancies to prevent the migration and disappearance of vacancies. The addition of Be significantly increases the nucleation rate of the metastable phase, improves the strengthening effect of aging, and reduces the solid solubility of the above elements in the aluminum matrix. Ni and Be are complexed, which greatly promotes the precipitation of the second phase and reduces the solid solubility of the alloying elements in the matrix. (10) When the mass percentage content of RE is 0.0001-0.1%, RE can form a rare earth active film on the surface of the Fe-containing phase or combine with Al, Fe, Ti and other atoms to form rare earth compounds to effectively reduce the solid solution of harmful elements in the aluminum matrix. It can also transform the long strip β-Fe phase into the spherical α-Fe phase and transform the elemental Si. On the other hand, RE can also promote the precipitation of dispersed phases such as CuAl2, (CuMg)Al2, Mg2Si, etc., and improve the mechanical properties of aluminum alloys. In addition, RE can also refine the grains, second phases and precipitated phases (for example, it can refine Al3RE, Al3Fe, Mg2Si phases, etc.), further improving the mechanical properties and thermal conductivity of aluminum alloys.
[0037] When the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni within the above content range is not more than 9%, and when the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%, Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni interact with each other as a whole, and can remove the content of transition elements Ti, Mn, Cr, and V in the aluminum matrix that have a great influence on thermal conductivity, refine the grains, reduce the solid solubility of alloy elements in the aluminum matrix, and increase the volume fraction of the precipitated phase, so as to reduce the adverse effects of alloy elements on the thermal conductivity of the aluminum alloy and improve the comprehensive properties of the aluminum alloy (including mechanical properties, thermal conductivity, and forming properties, etc.). At the same time, under the further action of aging treatment, the solid solubility of each element in the aluminum matrix is further reduced, which can eliminate the adverse effects of alloy elements on the thermal conductivity of aluminum alloy as much as possible, and the second phase (such as Al3Fe, Mg2Si, Al2Cu, AlFeSiNi, AlMnSi phases, etc.) can also be refined in the aluminum matrix and at the grain boundaries or within the grain boundaries, which greatly improves the mechanical properties and thermal conductivity of aluminum alloy.
[0038] Specifically, since transition elements such as Mn, Cr, Ti, and V have a great influence on the thermal conductivity and mechanical properties of aluminum alloys, their content needs to be strictly controlled; when the amount of elements such as Cu, Mg, and Zn added is large, the thermal conductivity and mechanical properties of aluminum alloys will also be reduced, and their content also needs to be controlled; but when the mass percentage content of at least one of Cu, Mg, Sr, Zn, Co, Be, RE, Ni, Mn, Cr, Ti, and V is low, the elements with a low mass percentage are not easy to precipitate, and will exist in the aluminum matrix in the form of solid solution, thereby reducing the thermal conductivity and mechanical properties of the aluminum alloy, and the refinement and modification effect of the aluminum alloy will also deteriorate, causing the single Si at the grain boundary of the aluminum alloy to exist in the form of coarse flakes and strips, seriously splitting the aluminum matrix, and further reducing the thermal conductivity and mechanical properties of the aluminum alloy. In the present invention, as described in the above items (1) to (10), Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni within the above content range interact with each other as a whole to refine the grains (such as the modification effect of Sr, the grain refining effect of Ni, Co, Be, and RE), reduce each other's solid solubility in the aluminum matrix (such as the elements can react with each other to form a second phase), and increase the volume fraction of the precipitated phase (such as Cu, Mg, Sr, Zn, Co, Be, RE, and Ni can promote the precipitation of the second phase), so as to improve the mechanical properties and thermal conductivity of the aluminum alloy; even if the mass percentage content of one or some elements is low, during the aging treatment, all or almost all of the elements can be precipitated, avoiding adverse effects on the thermal conductivity of the aluminum alloy.
[0039] It can be understood that since the addition of alloying elements will reduce the thermal conductivity of aluminum alloys, the amount of at least one element added among Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni in the present invention may be less than the amount of the element added in the prior art, and the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%. Among them, the amount of all elements added among Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni in the present invention may be less than the amount of the elements added in the prior art. Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni within the above content range interact and influence each other as a whole. On the one hand, it can avoid the addition of too many elements to reduce the thermal conductivity of the aluminum alloy. On the other hand, when at least one of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is added in a small amount, the comprehensive properties of the aluminum alloy (including mechanical properties and thermal conductivity, etc.) can still be improved.
[0040] The Al-Si-Fe-Mg high thermal conductivity aluminum alloy also contains 0-0.009% In by mass, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, or 0.009%.
[0041] The sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, In and Ni is not more than 9%, preferably not more than 8.6%, and more preferably not more than 8.1%. In this way, while ensuring the excellent mechanical properties and thermal conductivity of the aluminum alloy, it is avoided that too many elements are added to form a solid solution in the aluminum matrix. In one embodiment, the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, In and Ni is 5.5-9%, preferably 6-8.6%, more preferably 6.5-7.05%, and specifically 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, or 9%.
[0042] The mass ratio of Cu to In is 0.2-40:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties of the aluminum alloy gradually increase. The mass ratio of Cu to In is preferably 1-20:1, more preferably 5-10:1, specifically 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 25:1, 30:1, 35:1, or 40:1.
[0043] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains 0-0.009% by mass of In. On the one hand, In can improve the mechanical properties of the aluminum alloy. On the other hand, In can react with other elements as much as possible to form a second phase to avoid the adverse effect of Si dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, In can react with Al and Cu to form second phases such as AlIn and CuIn. In addition, In can also refine the grains to improve the elongation of the aluminum alloy.
[0044] The Al-Si-Fe-Mg high thermal conductivity aluminum alloy further contains 0-0.005% by mass of Nb, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, or 0.005%.
[0045] The mass ratio of Ni to Nb is 0.1-10:1. Within this range, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Ni to Nb is preferably 0.5-5:1, more preferably 1-3:1, specifically 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0046] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains 0-0.005% by mass of Nb. On the one hand, Nb can improve the mechanical properties and thermal conductivity of the aluminum alloy. On the other hand, Nb can react with other elements as much as possible to form a second phase to avoid the adverse effect of Nb dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Nb can react with Ti and Al to form a TiAl-Nb phase. In addition, Nb can also refine the grains to improve the elongation of the aluminum alloy.
[0047] The Al-Si-Fe-Mg high thermal conductivity aluminum alloy also contains Bi in a mass percentage content of 0-0.01%, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, or 0.01%.
[0048] The mass ratio of Mg to Bi is 5-400:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties of the aluminum alloy gradually increase. The mass ratio of Mg to Bi is preferably 50-300:1, more preferably 100-200:1, and more preferably 150-200:1, and specifically can be 5:1, 10:1, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, or 400:1.
[0049] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains Bi with a mass percentage of 0-0.01%. On the one hand, Bi can improve the mechanical properties of the aluminum alloy. On the other hand, Bi can react with other elements as much as possible to form a second phase to avoid the adverse effect of Bi dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Bi can react with Mg and Cd to form second phases such as Mg3Bi2 and Mg3(BiCd)2.
[0050] The Al-Si-Fe-Mg high thermal conductivity aluminum alloy further contains Ge in a mass percentage content of 0-0.005%, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, or 0.005%.
[0051] The sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, In, Ge, Bi and Ni is not more than 9.01%, preferably not more than 8.6%, and more preferably not more than 8.1%. In this way, while ensuring the excellent mechanical properties and thermal conductivity of the aluminum alloy, it is avoided that too many elements are added to form a solid solution in the aluminum matrix. In one embodiment, the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, In, Ge, Bi and Ni is 5.5-9%, preferably 6-8.6%, more preferably 6.5-7%, and specifically 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, or 9%.
[0052] The mass ratio of Si to Ge is 1000-2000:1. Within the range of this mass ratio, as the mass ratio decreases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Si to Ge is preferably 1000-1500:1, more preferably 1300-1500:1, and specifically can be 1000:1, 1100:1, 1200:1, 1300:1, 1400:1, 1500:1, 1600:1, 1700:1, 1800:1, 1900:1, 2000:1.
[0053] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains Ge with a mass percentage content of 0-0.005%. On the one hand, Ge can improve the mechanical properties and thermal conductivity of the aluminum alloy. On the other hand, Ge can react with other elements as much as possible to form a second phase to avoid the adverse effect of Ge dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Ge can react with Al and Si to form Al9Ge7, Al6Ge5, Al5Ge2, Al3Ge4, SiGe and other second phases. In addition, Ge can promote the precipitation of second phases such as Mg2Si and CuAl2, refine the precipitation phase, and reduce the solubility of the above elements in the aluminum matrix. Ge can also replace part of the Si atoms in the metastable precipitation phase. The Si-Ge phase precipitated at the initial stage of aging provides a nucleation site for the θ phase, increasing the density of the θ phase, to further improve the mechanical properties and thermal conductivity of the aluminum alloy.
[0054] The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains 0-0.005% by mass of Mo, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, or 0.005%.
[0055] The mass ratio of Si to Mo is 1500-2000:1. Within the mass ratio range, as the mass ratio decreases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Si to Mo is preferably 1500-1800:1, more preferably 1500-1600:1, specifically 1500:1, 1600:1, 1700:1, 1800:1, 1900:1, or 2000:1.
[0056] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains 0-0.005% by mass of Mo. On the one hand, Mo can improve the mechanical properties and thermal conductivity of the aluminum alloy. On the other hand, Mo can react with other elements to form a second phase as much as possible to avoid the adverse effect of Ge dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Mo can react with Al, Si, Fe, etc. to form AlMo, AlSiMo, AlSiFeMo and other second phases, which are dispersed in the aluminum matrix grain boundaries. In addition, Mo can also refine the grains, improve the morphology of Fe-containing intermetallic compounds, and further improve the mechanical properties of the aluminum alloy.
[0057] The Al-Si-Fe-Mg high thermal conductivity aluminum alloy also contains Ag in a mass percentage content of 0-0.005%, specifically 0.0001%, 0.0005%, 0.001%, 0.002%, 0.003%, 0.004%, or 0.005%.
[0058] The mass ratio of Mg to Ag is 10-1000:1. Within this range, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Mg to Ag is preferably 50-800:1, more preferably 200-500:1, and more preferably 400-500:1. Specifically, it can be 10:1, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500:1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1 or 1000:1.
[0059] The mass ratio of Cu to Ag is 1-500:1. Within the range of this mass ratio, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase with the increase of the mass ratio. The mass ratio of Cu to Ag is preferably 5-300:1, more preferably 10-150:1, and more preferably 20-50:1. Specifically, it can be 1:1, 5:1, 10:1, 50:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, or 500:1.
[0060] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains 0-0.005% Ag by mass. Ag can promote the precipitation of the second phase (such as Al2Cu, Mg2Si, Mg3Sn2, and Mg3Bi2, etc.), refine the precipitation phase and increase the density of the precipitation phase, thereby improving the precipitation strengthening effect of the aluminum alloy, thereby improving the mechanical properties and thermal conductivity of the aluminum alloy.
[0061] The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Sn with a mass percentage content of 0-0.15% and Te with a mass percentage content of 0-0.005%.
[0062] The mass ratio of Mg to Sn is 0.5-15:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Mg to Sn is preferably 1-8:1, more preferably 3-8:1, and more preferably 5-8:1, and specifically can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or 15:1.
[0063] The mass ratio of Te to Sn is 0.01-1:1. Within this range, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of Te to Sn is preferably 0.05-1:1, more preferably 0.1-8:1, and more preferably 1-5:1, and specifically can be 0.01:1, 0.02:1, 0.04:1, 0.06:1, 0.08:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, or 1:1.
[0064] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains Sn with a mass percentage content of 0-0.15% and Te with a mass percentage content of 0-0.005%. Te can improve the mechanical properties and thermal conductivity of the aluminum alloy. Te can reduce the solidification temperature range of the aluminum alloy, form fine petal-shaped rather than dendritic primary crystals, reduce or eliminate micro-shrinkage, and thus improve the mechanical properties and thermal conductivity of the aluminum alloy. Sn can improve the thermal conductivity of the aluminum alloy, and can also react with other elements as much as possible to generate a second phase to avoid the adverse effect of Ge dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Sn can react with Al to generate a variety of high-temperature strengthening phases such as Al9Sn7, Al6Sn5, Al5Sn2, and Al3Sn4.
[0065] The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Cd in a mass percentage content of 0-0.01%.
[0066] The mass percentage content of Cd may be 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, or 0.01%.
[0067] The mass ratio of RE, Sr, and Fe is 0.002-0.1:0.02-0.08:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of RE, Sr, and Fe is preferably 0.005-0.05:0.04-0.06:1, and more preferably 0.01-0.03:0.05-0.06:1, and specifically 0.002:0.02:1, 0.002:0.04:1, 0.002:0.06:1, 0.002:0.08:1, 0.005:0.02:1, 0.005:0.04:1, 0.005:0.0 6:1, 0.005:0.08:1, 0.01:0.02:1, 0.01:0.04:1, 0.01:0.06:1, 0.01:0.08:1, 0.05:0.02:1, 0.05:0.04:1, 0.05:0.06:1, 0.05:0.08:1, 0.1:0.02:1, 0.1:0.04:1, 0.1:0.06:1, or 0.1:0.08:1.
[0068] The mass ratio of RE to Cd is 0.1-25:1. Within the range of this mass ratio, as the mass ratio increases, the mechanical properties and thermal conductivity of the aluminum alloy gradually increase. The mass ratio of RE to Cd is preferably 1-20:1, more preferably 5-20:1, and more preferably 10-15:1, and specifically can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1, or 25:1.
[0069] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains Cd with a mass percentage of 0-0.01%. Cd can refine α-Al and can form strengthening phases such as REAl2Cd3, Al3Cd, Al2Cd3, (CuCd)Al2, Mg2(SiCdREFe), Mg3(BiCd)2 with Al, RE, Cu, Mg, Si, Fe, and Bi to reduce the solid solubility of each other in the aluminum matrix and increase the volume fraction of the precipitated phase. Cd will form a large number of Cd-vacancy clusters in the aging stage, promote and accelerate the precipitation of CuAl2 phase, and reduce the solid solubility of the above elements in the aluminum matrix.
[0070] In one embodiment, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.05-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, 0.001-0.05% Ni by mass, 0.001-0.05% Co by mass, 0.001-0.01% Be by mass, 0.0001-0.009% In by mass, 0.0001-0.005% Nb by mass, 0.0001-0.006% Bi by mass, and 0. 0.0001-0.005% Ge, 0.0001-0.005% Mo, 0.0001-0.005% Ag, 0.0001-0.1% Sn, 0.0001-0.005% Te, 0.001-0.01% Cd, and 0.001-0.0 5% RE, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%, the mass ratio of Be, Co, and Fe is 0.001-0.03:0.004-0.25:1, and the mass ratio of Co, Ni, and Be is 0.1-100:0.4-50:1.
[0071] In another embodiment, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.05-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, and 0.001-0.05% Ni by mass. , Co with a mass percentage of 0.001-0.1%, Be with a mass percentage of 0.001-0.01%, Mn with a mass percentage of 0.001-0.009%, Ti with a mass percentage of 0.001-0.008%, Cr with a mass percentage of 0.001-0.008%, V with a mass percentage of 0.0001-0.009%, In with a mass percentage of 0.00 0.01-0.005% Nb, 0.0001-0.006% Bi, 0.0001-0.005% Ge, 0.0001-0.005% Mo, 0.0001-0.005% Ag, 0.0001-0.1% Sn, 0.0001-0.005% Te, 0.001-0.0 1% Cd and 0.001-0.05% RE by mass, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%, the mass ratio of Be, Co, and Fe is 0.001-0.03:0.004-0.25:1, and the mass ratio of Co, Ni, and Be is 0.1-100:0.4-50:1.
[0072] In another embodiment, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 6-7.5% Si by mass, 0.5-0.7% Fe by mass, 0.005-0.04% Cu by mass, 0.1-0.3% Mg by mass, 0.01-0.03% Sr by mass, 0.002-0.01% Zn by mass, and 0.001-0.009% Cu by mass. Ni, Co with a mass percentage of 0.005-0.05%, Be with a mass percentage of 0.005-0.05%, Mn with a mass percentage of 0.001-0.009%, Ti with a mass percentage of 0.001-0.008%, Cr with a mass percentage of 0.001-0.008%, V with a mass percentage of 0.0001-0.009%, In with a mass percentage of 0.0001-0.009%, The content of Nb is 0.0001-0.005% by mass, the content of Bi is 0.0001-0.006% by mass, the content of Ge is 0.0001-0.005% by mass, the content of Mo is 0.0001-0.005% by mass, the content of Ag is 0.0001-0.005% by mass, the content of Sn is 0.0001-0.1% by mass, the content of Te is 0.0001-0.005% by mass, and the content of Cu is 0.0001-0.005% by mass. 01-0.01% Cd and 0.001-0.02% RE by mass, wherein the sum of the mass percentages of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE and Ni is 5.5-9%, the sum of the mass percentages of Cu, Mg and Zn is 0.18-0.3%, the mass ratio of Be, Co and Fe is 0.01-0.02:0.05-0.2:1, and the mass ratio of Co, Ni and Be is 1-50:1-30:1.
[0073] The present invention also provides a method for preparing an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, comprising the following steps: The aluminum source is heated at a temperature of 720-780°C to obtain aluminum liquid, wherein the aluminum liquid may contain Mn, Cr, Ti, and V; Adding Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni to the aluminum liquid, performing a second heating treatment, and keeping the temperature at 700-750° C. for 10-30 minutes to obtain an alloy liquid; After refining, degassing, and slagging the alloy liquid, the composition and content are tested; and After the composition and content are tested to be qualified, the alloy liquid is subjected to die casting treatment and aging treatment to obtain Al-Si-Fe-Mg series high thermal conductivity aluminum alloy. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.05-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, 0.001-0.05% Ni by mass, 0-0.1% Co by mass, 0-0.01% Be by mass, and 0.0001-0.1% RE by mass, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%.
[0074] The aluminum source is at least one of original aluminum, aluminum ingot, and recycled aluminum. The impurities usually contained in the aluminum source include Mn, Ti, Cr, or V.
[0075] Liquid aluminum produced by industrial aluminum electrolytic cells, after purification, clarification and slag removal, is cast into commercial aluminum ingots, which generally contain no more than 99.8% aluminum, and are called primary aluminum. Aluminum ingots are alloys prepared by adding other elements such as Si, Cu, Mg, Fe, etc., based on pure aluminum and recycled aluminum as raw materials in accordance with international standards or special requirements to improve the casting, chemical and physical properties of pure aluminum. Recycled aluminum, also known as "secondary aluminum", is an aluminum alloy or aluminum metal obtained by remelting and refining waste aluminum, waste aluminum alloy materials, or aluminum-containing waste. The main raw materials for smelting recycled aluminum are industrial depreciation waste aluminum parts (such as aircraft waste parts and engines, casing covers, etc.) and waste aluminum materials (including plates, pipes, bars, profiles, scraps, foils, etc.) generated during aluminum processing. It can be understood that the aluminum source can also be an aluminum source other than primary aluminum, aluminum ingots, and recycled aluminum.
[0076] At least one of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni may be added in the form of an alloy or a single substance.
[0077] The method for preparing the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also includes the step of adding at least one of In, Nb, Bi, Ge, Mo, Ag, Sn, Te, and Cd to the aluminum liquid. At least one of In, Nb, Bi, Ge, Mo, Ag, Sn, Te, and Cd can be added in the form of an alloy or a single substance. The mass percentage content of In can be 0-0.009%. The mass percentage content of Nb is 0-0.005%. The mass percentage content of Bi can be 0-0.01%. The mass percentage content of Ge can be 0-0.005%. The mass percentage content of Mo can be 0-0.005%. The mass percentage content of Ag can be 0-0.005%. The mass percentage content of Sn can be 0-0.15%. The mass percentage content of Te can be 0-0.005%. The mass percentage content of Cd can be 0-0.01%.
[0078] In one embodiment, the aging treatment is performed at a temperature of 280 to 350° C. and for a time of 0.05 to 15 hours. The temperature of the aging treatment may specifically be 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C, or 350°C; the time of the aging treatment may specifically be 0.05h, 0.06h, 0.07h, 0.08h, 0.09h, 0.1h, 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.5h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, or 15h. During the aging treatment, the size of the precipitated phase gradually changes to a smaller size, and all or almost all of the alloying elements dissolved in the alloy are precipitated, increasing the pinning effect on dislocations and greatly improving the thermal conductivity and mechanical properties of the aluminum alloy.
[0079] In another embodiment, the aging treatment, which may also be referred to as a multi-stage aging treatment, includes a primary low-temperature aging treatment, a secondary low-temperature aging treatment, and a tertiary high-temperature aging treatment. The temperature of the primary low-temperature aging treatment is -100°C to -200°C, and the time is 1 to 15 hours; the temperature of the secondary low-temperature aging treatment is 0 to 70°C, and the time is 1 to 24 hours; the temperature of the tertiary high-temperature aging treatment is 280 to 350°C, and the time is 0.05 to 15 hours. The temperature of the primary low-temperature aging treatment may specifically be -200°C, -190°C, -180°C, -170°C, -160°C, -150°C, -140°C, -130°C, -120°C, -110°C, or -100°C. The time of the primary low-temperature aging treatment may be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, or 15h. The temperature of the secondary low-temperature aging treatment may be 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, or 70°C. The time of the secondary low-temperature aging treatment may be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, or 24h. The temperature of the three-stage high-temperature aging treatment can be 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 330°C, 335°C, 340°C, 345°C, or 350°C. The time of the three-stage high-temperature aging treatment can be 0.05h, 0.06h, 0.07h, 0.08h, 0.09h, 0.1h, 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.5h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, or 15h.
[0080] During the primary low-temperature aging treatment, deep cryogenic treatment can inhibit the segregation of atoms such as Mg, Cu, Ni and Si, and at the same time make the alloy produce a greater degree of supercooling, significantly increase the range of the GP zone, facilitate the subsequent high-temperature process to increase the nucleation rate, and the alloy elements can be more fully precipitated. Aluminum alloys also undergo volume and lattice contraction during the low-temperature process, the supersaturation of alloy elements increases, solute atoms will precipitate in the alloy, and the content of alloy elements participating in aging will be increased. The reduction in the solubility of solute atoms will cause the solute atoms to segregate at dislocations, significantly increasing the formation of the GP zone. During the secondary low-temperature aging treatment, the atomic segregation under the action of internal stress and dislocation will diffuse uniformly and dispersedly in the aluminum matrix and grain boundaries. During the tertiary high-temperature aging treatment, the GP zone gradually transforms into a precipitation phase with a smaller size but a larger volume fraction, which precipitates all or almost all of the alloy elements dissolved in the alloy, increases the pinning effect on dislocations, and greatly improves the thermal conductivity and mechanical properties of aluminum alloys.
[0081] The alloy liquid is die-casted at a temperature of 660-700°C, wherein the die-casting speed of the die-casting machine is 0.23-2.5 m / s. It can be understood that the die-casting process of the present invention is a common die-casting process, and vacuum die-casting can also be used to die-cast the alloy liquid. The strength (such as yield strength and tensile strength) and elongation of the aluminum alloy after vacuum die-casting will be higher than the strength (such as yield strength and tensile strength) and elongation of the aluminum alloy after common die-casting.
[0082] The temperature of the refining treatment is 690-750°C, and the time is 10-20 minutes. The refining agent of the refining treatment includes the following raw materials in parts by weight: 60-70 parts of KF, 50-60 parts of NaCl, 40-60 parts of LiCl, 20-25 parts of cryolite, 10-25 parts of AIF3, 10-15 parts of CaF2, 5-10 parts of light calcium carbonate, 15-20 parts of graphite powder, 10-20 parts of talcum powder, 20-30 parts of MgCl2, and 10-30 parts of rare earth acid salt. The rare earth acid salt is one of the chlorides, fluorides, and nitric acid compounds of light rare earths, or a combination thereof. The rare earth acid salt can be one of the chlorides, fluorides, and nitric acid compounds of heavy rare earths, or a combination thereof. The mass ratio of the refining agent to the alloy liquid is 0.0013-0.0018:1.
[0083] It can be understood that when the content of each component in the alloy liquid after degassing and slag removal treatment meets the standard, subsequent treatments such as die casting are carried out. Among them, the qualified aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.05-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, 0.001-0.05% Ni by mass, 0-0.1% Co by mass, 0-0.01% Be by mass, 0.0001-0.1% RE by mass, and Al and unavoidable impurities, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%. When the test fails, the corresponding elements can be added to adjust until the composition and content are qualified.
[0084] In the technical solution of the present invention, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy prepared by the preparation method of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.05-0.4% Mg by mass, 0.005-0.04% Sr by mass, and 0.00 1-0.05% Zn, 0.001-0.05% Ni, 0-0.1% Co, 0-0.01% Be, and 0.0001-0.1% RE, wherein the sum of the mass percentages of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is no more than 9%, and the sum of the mass percentages of Cu, Mg, and Zn is 0.052-0.5%. Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni within the above content range interact with each other as a whole, ensuring that the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy has better formability and also has excellent mechanical properties and thermal conductivity. The details are as follows: (1) When the mass percentage content of Si is 5-8%, on the one hand, Si can improve the fluidity and density of aluminum alloy, thereby improving the forming performance and mechanical properties of aluminum alloy. On the other hand, Si can react with other elements as much as possible to form a second phase to avoid the adverse effect of Si dissolved in the aluminum matrix on the thermal conductivity of aluminum alloy. Specifically, Si can react with Al, Fe, Cu, Mg, Mn, etc. to form Mg2Si, AlFeSi, AlMnSi, AlFeSiCu, AlFeMgSi, AlFeMnSi and other second phases; (2) When the mass percentage of Fe is 0.4-0.8%, on the one hand, Fe can reduce the sticking tendency of aluminum alloy castings and improve the mechanical properties and thermal conductivity of aluminum alloys. On the other hand, Fe can react with other elements as much as possible to form a second phase to avoid the adverse effect of Fe dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Fe can react with Al, Si, Mg, Cu, Mn, Ni, etc. to form Al3Fe, AlFeSi, AlFeMgSi, AlFeSiCu, AlFeSiNi, AlFeMgSiNi, AlFeMnSi, FeNiAl9 and other second phases; (3) When the mass percentage of Cu is 0.001-0.05%, on the one hand, Cu can improve the mechanical properties, thermal conductivity, and fatigue resistance of aluminum alloys. On the other hand, Cu can react with other elements to form a second phase as much as possible to avoid the adverse effect of Cu dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Cu can react with Al, Fe, Si, Mg, Zn, etc. to form second phases such as CuAl2, AlFeSiCu, Al2CuZn, (CuMg)Al2, etc. In addition, Cu can also promote the precipitation of second phases such as Mg2Si, Mg2Zn, Mg2SiZn, (CuMg)Al2, AlFeMgSi, AlFeMgSiNi, etc., increase their volume fraction and dispersion, and reduce the solid solubility of the above elements in the aluminum matrix; (4) When the mass percentage content of Mg is 0.05-0.4%, on the one hand, Mg can improve the mechanical properties and thermal conductivity of aluminum alloys, and on the other hand, Mg can react with other elements to form a second phase as much as possible to avoid the adverse effect of Mg dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Specifically, Mg can react with Al, Fe, Si, Cu, Zn, Ni, etc. to form second phases such as Mg2Si, Mg2Zn, Mg2SiZn, (CuMg)Al2, AlFeMgSi, AlFeMgSiNi, etc. Mg can also promote the precipitation of second phases such as CuAl2, AlFeSiCu, Al2CuZn, (CuMg)Al2, increase their volume fraction and dispersion, and reduce the solid solubility of the above elements in the aluminum matrix; (5) When the mass percentage of Sr is 0.005-0.04%, on the one hand, Sr can be modified through the heterogeneous nucleation theory or twin valley mechanism to refine the second phase such as eutectic silicon, improve the thermal conductivity and mechanical properties of the aluminum alloy, and transform the β-AlFeSi phase in the ingot into the Chinese character α-AlFeSi phase to improve the mechanical properties of the aluminum alloy. On the other hand, Sr can preferentially combine with Fe, Cu, Mn, Cr, Si and other elements to form dispersion strengthening to avoid the adverse effect of Sr dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. In addition, Sr can also promote the precipitation of CuAl2, Mg2Si and other phases to reduce the solid solubility of these alloy elements in the aluminum matrix; (6) When the mass percentage of Zn is 0.001-0.05%, on the one hand, Zn can improve the mechanical properties of aluminum alloys, and on the other hand, Zn can react with other elements to form a second phase as much as possible to avoid the adverse effect of Zn dissolved in the aluminum matrix on the thermal conductivity of the aluminum alloy. Specifically, Zn can react with Al, Mg, Cu and Si to form second phases such as MgZn2, Mg2SiZn, Al2CuZn, etc. In addition, Zn can eliminate elemental Si to reduce the adverse effect of elemental Si on the performance of aluminum alloys. Zn can also promote the precipitation of phases such as Mg2Si and Al2Cu, thereby improving mechanical properties and thermal conductivity. (7) When the mass percentage of Ni is 0.001-0.05%, on the one hand, Ni can be used to improve the mechanical properties and thermal conductivity of aluminum alloys. On the other hand, Ni can react with other elements to form a second phase as much as possible to avoid the adverse effect of Ni dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Specifically, Ni can react with Al, Fe, Mg, Si, etc. to form second phases such as Al3Ni, AlFeSiNi, AlFeMgSiNi, FeNiAl9, etc., to promote the precipitation of elements such as Cu, Mg, Zn, Si, Fe, etc. dissolved in the alloy; Ni can also refine grains, promote the precipitation of strengthening phases such as CuAl2, (CuMg)Al2, Mg2Si, increase the volume fraction and dispersion of the precipitated phase, and reduce the solid solubility of alloy elements in the aluminum matrix. In addition, Ni and Cu and Mg can promote each other's precipitation to improve the thermal conductivity and mechanical properties of aluminum alloys. (8) When the mass percentage of Co is not more than 0.1%, Co can refine the grains to improve the thermal conductivity and mechanical properties of aluminum alloys. On the other hand, it can also react with other elements to form a second phase as much as possible to avoid the adverse effect of Be dissolved in the aluminum matrix on the thermal conductivity of aluminum alloys. Specifically, Co can react with Al, Fe, Si, etc. to form Al 15(Fe, Co)3Si2, Al3(Fe, Co) and other second phases. In addition, Co has a refining effect on the Al3Fe phase, which can transform the coarse needle-shaped and flake-shaped β-Al3Fe phase into small flower-shaped and fine strip-shaped α-Al 15 (Fe,Co)3Si2 phase can also promote the α-Al 15 The precipitation of (Fe, Co)3Si2 phase further improves the mechanical properties and thermal conductivity of aluminum alloy. The composite addition of Ni and Co can effectively modify Fe and transform free Fe into the second phase. The composite addition of Co, Ni and Be can quickly reduce the solid solubility of each other in the alloy and increase the volume fraction of the second phase to improve the mechanical properties and thermal conductivity of aluminum alloy. (9) When the mass percentage content of Be is not more than 0.01%, Be can transform the eutectic Si phase from a lamellar phase to a fine phase to refine the Si phase, thereby reducing or eliminating the adverse effects of Si on the aluminum alloy. Be can also transform the plate-like β intermediate phase into a relatively harmless Chinese character-shaped Be-Fe (Al8Fe2SiBe) phase to reduce or eliminate the adverse effects of Fe on the performance of the aluminum alloy. It can also reduce the formation of Mg-containing Fe-rich phases, thereby increasing the Mg content in the aging process. On the other hand, Be can combine with vacancies to prevent the migration and disappearance of vacancies. The addition of Be significantly increases the nucleation rate of the metastable phase, improves the strengthening effect of aging, and reduces the solid solubility of the above elements in the aluminum matrix. Ni and Be are complexed, which greatly promotes the precipitation of the second phase and reduces the solid solubility of the alloying elements in the matrix. (10) When the mass percentage content of RE is 0.0001-0.1%, RE can form a rare earth active film on the surface of the Fe-containing phase or combine with Al, Fe, Ti and other atoms to form rare earth compounds to effectively reduce the solid solution of harmful elements in the aluminum matrix. It can also transform the long strip β-Fe phase into the spherical α-Fe phase and transform the elemental Si. On the other hand, RE can also promote the precipitation of dispersed phases such as CuAl2, (CuMg)Al2, Mg2Si, etc., and improve the mechanical properties of aluminum alloys. In addition, RE can also refine the grains, second phases and precipitated phases (for example, it can refine Al3RE, Al3Fe, Mg2Si phases, etc.), further improving the mechanical properties and thermal conductivity of aluminum alloys.
[0085] When the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni within the above content range is not more than 9%, and when the sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%, Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni interact with each other as a whole, and can remove the content of transition elements Ti, Mn, Cr, and V in the aluminum matrix that have a great influence on thermal conductivity, refine the grains, reduce the solid solubility of alloy elements in the aluminum matrix, and increase the volume fraction of the precipitated phase, so as to reduce the adverse effects of alloy elements on the thermal conductivity of the aluminum alloy and improve the comprehensive properties of the aluminum alloy (including mechanical properties, thermal conductivity, and forming properties, etc.). At the same time, under the further action of aging treatment, the solid solubility of each element in the aluminum matrix is further reduced, which can eliminate the adverse effects of alloy elements on the thermal conductivity of aluminum alloy as much as possible, and the second phase (such as Al3Fe, Mg2Si, Al2Cu, AlFeSiNi, AlMnSi phases, etc.) can also be refined in the aluminum matrix and at the grain boundaries or within the grain boundaries, which greatly improves the mechanical properties and thermal conductivity of aluminum alloy.
[0086] The present invention also provides a heat dissipation structure. At least part of the heat dissipation structure is made of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy or the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy prepared by the preparation method of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy. The heat dissipation structure has excellent thermal conductivity and mechanical properties. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy has excellent elongation and is suitable for making different structures by various processes.
[0087] The heat dissipation structure can be a filter housing of a communication base station, a heat dissipation substrate of a communication base station, a cabinet housing of a communication base station, a housing of a three-electric structure of a car, a housing of a car, a heat sink of a computer device, a middle plate of a mobile phone, a housing of a mobile phone, a heat sink of an LED lamp, a thin part of a 5G product, etc. Since the heat dissipation structure adopts all the technical solutions of all the embodiments of the above-mentioned Al-Si series die-casting aluminum alloy, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here.
[0088] Embodiment 1 The aluminum source is heated at a temperature of 720° C. to obtain aluminum liquid; Adding Si, Fe, Cu, Mg, Sr, Zn, RE, and Ni to the aluminum liquid, and keeping the temperature at 700° C. for 30 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of Example 1. In the aging treatment, the temperature of the first-level low-temperature aging treatment is -200°C and the time is 1h; the temperature of the second-level low-temperature aging treatment is 10°C and the time is 3h; the temperature of the third-level high-temperature aging treatment is 300°C and the time is 5h. The alloy liquid is subjected to die casting treatment at a temperature of 660ºC, wherein the die casting speed of the die casting machine is 0.5m / s. The Al-Si-Fe-Mg high thermal conductivity aluminum alloy contains 5% Si by mass, 0.8% Fe by mass, 0.005% Cu by mass, 0.2% Mg by mass, 0.02% Sr by mass, 0.005% Zn by mass, 0.005% Ni by mass, and 0.01% RE by mass, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, RE, and Ni is 6.045%, and the sum of the mass percentage contents of Cu, Mg, and Zn is 0.21%.
[0089] Comparative Example 1 The aluminum source is heated at a temperature of 720° C. to obtain aluminum liquid; Adding Si, Fe, Cu, Sr, Zn, RE, and Ni to the aluminum liquid, and keeping the temperature at 700° C. for 30 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of comparative example 1. In the aging treatment, the temperature of the first low temperature aging treatment is -200°C and the time is 1h; the temperature of the second low temperature aging treatment is 10°C and the time is 3h; the temperature of the third high temperature aging treatment is 300°C and the time is 5h. The alloy liquid is subjected to die casting treatment at a temperature of 660ºC, wherein the die casting speed of the die casting machine is 0.5m / s. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Si with a mass percentage content of 5%, Fe with a mass percentage content of 0.8%, Cu with a mass percentage content of 0.005%, Sr with a mass percentage content of 0.02%, Zn with a mass percentage content of 0.005%, Ni with a mass percentage content of 0.005%, and RE with a mass percentage content of 0.01%.
[0090] Comparative Example 2 The aluminum source is heated at a temperature of 720° C. to obtain aluminum liquid; Adding Si, Fe, Cu, Mg, Sr, Zn, RE, and Ni to the aluminum liquid, and keeping the temperature at 700° C. for 30 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of comparative example 2. In the aging treatment, the temperature is 250°C and the time is 6h. The alloy liquid is subjected to die casting treatment at a temperature of 660ºC, wherein the die casting speed of the die casting machine is 0.5m / s. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Si with a mass percentage content of 5%, Fe with a mass percentage content of 0.8%, Cu with a mass percentage content of 0.005%, Mg with a mass percentage content of 0.2%, Sr with a mass percentage content of 0.02%, Zn with a mass percentage content of 0.005%, Ni with a mass percentage content of 0.005%, and RE with a mass percentage content of 0.01%.
[0091] Embodiment 2 The aluminum source is heated at a temperature of 780° C. to obtain aluminum liquid, wherein the aluminum liquid may contain Mn, Cr, Ti, and V; Adding Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni to the aluminum liquid, and keeping the temperature at 750° C. for 10 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of Example 2. The temperature of the aging treatment is 310°C and the time is 4h. The alloy liquid is subjected to die casting treatment at a temperature of 700ºC, wherein the die casting speed of the die casting machine is 2.5m / s. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 8% Si by mass, 0.4% Fe by mass, 0.02% Cu by mass, 0.2% Mg by mass, 0.02% Sr by mass, 0.01% Zn by mass, 0.001% Ni by mass, 0.002% Co by mass, 0.002% Be by mass, 0.01% RE by mass, and 0.01% by mass. The mass percentage content of Mn is 0.002%, the mass percentage content of Ti is 0.001%, the mass percentage content of Cr is 0.002%, and the mass percentage content of V is 0.001%, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE and Ni is 8.665%, the sum of the mass percentage contents of Cu, Mg and Zn is 0.23%, the mass ratio of Be, Co and Fe is 0.005:0.005:1, and the mass ratio of Co, Ni and Be is 1:0.5:1.
[0092] Embodiment 3 The aluminum source is heated at a temperature of 750° C. to obtain aluminum liquid, wherein the aluminum liquid may contain Mn, Cr, Ti, and V; Adding Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni to the aluminum liquid, and keeping the temperature at 730° C. for 15 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of Example 3. In the aging treatment, the temperature of the first-level low-temperature aging treatment is -100°C and the time is 5h; the temperature of the second-level low-temperature aging treatment is 50°C and the time is 1h; the temperature of the third-level high-temperature aging treatment is 320°C and the time is 3h. The alloy liquid is die-casted at a temperature of 670ºC, wherein the die-casting speed of the die-casting machine is 1m / s. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 6% Si by mass, 0.5% Fe by mass, 0.05% Cu by mass, 0.4% Mg by mass, 0.03% Sr by mass, 0.01% Zn by mass, 0.05% Ni by mass, 0.01% Co by mass, 0.01% Be by mass, 0.1% RE by mass, and 0.01% Ni by mass. The mass percentage content of Mn is 0.001%, the mass percentage content of Ti is 0.001%, the mass percentage content of Cr is 0.001%, and the mass percentage content of V is 0.001%, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE and Ni is 7.16%, the sum of the mass percentage contents of Cu, Mg and Zn is 0.46%, the mass ratio of Be, Co and Fe is 0.02:0.02:1, and the mass ratio of Co, Ni and Be is 1:5:1.
[0093] Embodiment 4 The aluminum source is heated at a temperature of 740° C. to obtain aluminum liquid, wherein the aluminum liquid may contain Mn, Cr, Ti, and V; Adding Si, Fe, Cu, Mg, Sr, Zn, Co, Be, In, Nb, Bi, Ge, RE, and Ni to the aluminum liquid, and keeping the temperature at 740° C. for 20 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of Example 4. In the aging treatment, the temperature of the first-level low-temperature aging treatment is -150°C and the time is 3h; the temperature of the second-level low-temperature aging treatment is 0°C and the time is 10h; the temperature of the third-level high-temperature aging treatment is 350°C and the time is 2h. The alloy liquid is die-casted at a temperature of 680ºC, wherein the die-casting speed of the die-casting machine is 2.5m / s. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 6% Si by mass, 0.5% Fe by mass, 0.05% Cu by mass, 0.2% Mg by mass, 0.03% Sr by mass, 0.01% Zn by mass, 0.05% Ni by mass, 0.01% Co by mass, 0.01% Be by mass, 0.0001% RE by mass, 0.001% Mn by mass, 0.001% Ti by mass, 0.01% Zn by mass, 0.01 ... The content of Cr is 0.001% by mass, the content of V is 0.001% by mass, the content of In is 0.005% by mass, the content of Nb is 0.005% by mass, the content of Bi is 0.01% by mass, and the content of Ge is 0.003% by mass, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE and Ni is 6.8601%, the sum of the mass percentage contents of Cu, Mg and Zn is 0.26%, the mass ratio of Be, Co and Fe is 0.02:0.02:1, and the mass ratio of Co, Ni and Be is 1:5:1.
[0094] Embodiment 5 The aluminum source is heated at a temperature of 750° C. to obtain aluminum liquid, wherein the aluminum liquid may contain Mn, Cr, Ti, and V; Add Si, Fe, Cu, Mg, Sr, Zn, Mo, Ag, Sn, Te, RE, and Ni to the aluminum liquid, and keep the temperature at 730° C. for 10 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of Example 5. In the aging treatment, the temperature of the first-level low-temperature aging treatment is -160°C and the time is 1h; the temperature of the second-level low-temperature aging treatment is 70°C and the time is 1h; the temperature of the third-level high-temperature aging treatment is 350°C and the time is 0.1h. The alloy liquid is die-casted at a temperature of 680ºC, wherein the die-casting speed of the die-casting machine is 1m / s. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5% Si by mass, 0.4% Fe by mass, 0.02% Cu by mass, 0.15% Mg by mass, 0.005% Sr by mass, 0.001% Zn by mass, 0.005% Ni by mass, 0.005% RE by mass, 0.001% Mn by mass, 0.001% Ti by mass, and 0.001% Cr by mass. , 0.001% V, 0.003% Mo, 0.001% Ag, 0.1% Sn and 0.002% Te, wherein the sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, RE and Ni is 5.586%, the sum of the mass percentage contents of Cu, Mg and Zn is 0.171%, the mass ratio of Be, Co and Fe is 0.0025:0.0025:1, and the mass ratio of Co, Ni and Be is 1:5:1.
[0095] Embodiment 6 The aluminum source is heated at a temperature of 750° C. to obtain aluminum liquid, wherein the aluminum liquid may contain Mn, Cr, Ti, and V; Adding Si, Fe, Cu, Mg, Sr, Zn, Be, Co, Cd, RE, and Ni to the aluminum liquid, and keeping the temperature at 750° C. for 10 minutes to obtain an alloy liquid; After the alloy liquid is subjected to refining treatment and slag removal treatment, it is subjected to die casting treatment and aging treatment to obtain the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy of Example 6. In the aging treatment, the temperature of the first-level low-temperature aging treatment is 170°C and the time is 7h; the temperature of the second-level low-temperature aging treatment is 25°C and the time is 4h; the temperature of the third-level high-temperature aging treatment is 300°C and the time is 3h. The alloy liquid is subjected to die casting treatment at a temperature of 670ºC, wherein the die casting speed of the die casting machine is 1m / s. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5.2% Si by mass, 0.45% Fe by mass, 0.03% Cu by mass, 0.18% Mg by mass, 0.01% Sr by mass, 0.02% Zn by mass, 0.005% Ni by mass, 0.003% Co by mass, 0.003% Be by mass, 0.001% Mn by mass, and 0. 001% Ti, 0.001% Cr, 0.001% V, 0.01% Cd and 0.01% RE, wherein the sum of the mass percentages of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE and Ni is 5.911%, the sum of the mass percentages of Cu, Mg and Zn is 0.23%, the mass ratio of Be, Co and Fe is 0.007:0.007:1, and the mass ratio of Co, Ni and Be is 1:1.7:1.
[0096] Table 1 Performance test results of Examples 1 to 6 and Comparative Examples 1 to 2 According to Table 1, the yield strength, elongation, and electrical conductivity of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloys of Examples 1 to 6 are better than those of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloys of Comparative Examples 1 to 2. Moreover, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloys of Examples 1 to 6 can simultaneously meet the following requirements: thermal conductivity greater than 200, yield strength greater than 130 MPa, and elongation greater than 16%, and have great market application prospects.
[0097] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. An Al-Si-Fe-Mg series high thermal conductivity aluminum alloy containing aluminum, characterized in that: The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.11-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, 0.001-0.05% Ni by mass, 0-0.1% Co by mass, 0-0.01% Cu by mass, 0.11-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, 0.001-0.05% Ni by mass, 0-0.1% Co by mass, 0.01-0.01% Cu ... % Be, and 0.0001-0.1% RE by mass percentage, the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy is subjected to die casting and aging treatment, the aging treatment includes a primary low-temperature aging treatment, a secondary low-temperature aging treatment, and a tertiary high-temperature aging treatment, wherein the temperature of the primary low-temperature aging treatment is -100°C to -200°C, and the time is 1h to 15h; the temperature of the secondary low-temperature aging treatment is 0°C to 70°C, and the time is 1h to 24h; the temperature of the tertiary high-temperature aging treatment is 280°C to 350°C, and the time is 0.05h to 15h.
2. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy according to claim 1, characterized in that: The sum of the mass percentage contents of Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni is not more than 9%.
3. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy according to claim 1, characterized in that: The sum of the mass percentage contents of Cu, Mg, and Zn is 0.052-0.5%.
4. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy according to claim 1, characterized in that: Meet at least one of the following conditions: The mass ratio of Si to Fe is 5-20:1; The mass ratio of Si to Sr is 200-1500:1; The mass ratio of Fe and Co is 1-250:1; The mass ratio of Mg to Cu is 1-50:1; The mass ratio of Mg, Cu, and Zn is 5-500:0.1-20:1; The mass ratio of Co, Ni, and Be is 0.1-100:0.4-50:1; The mass ratio of Be, Co, and Fe is 0.001-0.03:0.004-0.25:1; The sum of the mass percentage contents of Cu, Mg, Zn, and Ni is 0.057-0.55%; RE is at least one of La, Ce, Pr, Nd, Er, Sm, Y, and Gd; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Mn, Ti, Cr, and V, and the sum of the mass percentages of Mn, Ti, Cr, and V is not greater than 0.03%; The mass percentage content of a single impurity in the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy is less than 0.02%, and the sum of the mass percentage contents of the impurities is less than 0.1%.
5. The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy according to any one of claims 1 to 4, characterized in that: Meet at least one of the following conditions: The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains 0-0.009% by mass of In; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains 0-0.005% by mass of Nb; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Bi in a mass percentage content of 0-0.01%; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Ge in a mass percentage content of 0-0.005%; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Mo in a mass percentage content of 0-0.005%; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains Ag in a mass percentage content of 0-0.005%; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Sn in a mass percentage content of 0-0.15%; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also contains Te in a mass percentage content of 0-0.005%; The Al-Si-Fe-Mg series high thermal conductivity aluminum alloy further contains Cd in a mass percentage content of 0-0.01%.
6. The Al-Si-Fe-Mg based high thermal conductivity aluminum alloy according to claim 5, characterized in that: Meet at least one of the following conditions: When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains In, the mass ratio of Cu to In is 0.2-40:1; When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Nb, the mass ratio of Ni to Nb is 0.1-10:1; When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Bi, the mass ratio of Mg to Bi is 5-400:1; When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Ge, the mass ratio of Si to Ge is 1000-2000:1; When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Mo, the mass ratio of Si to Mo is 1500-2000:1; When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Ag, the mass ratio of Mg to Ag is 10-1000:1, and the mass ratio of Cu to Ag is 1-500:1; When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Sn and Te, the mass ratio of Mg to Sn is 0.5-15:1, and the mass ratio of Te to Sn is 0.01-1:1; When the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains Cd, the mass ratio of RE, Sr, and Fe is 0.002-0.1:0.02-0.08:1, and the mass ratio of RE to Cd is 0.1-25:
1.
7. The Al-Si-Fe-Mg based high thermal conductivity aluminum alloy according to claim 5, characterized in that: The Al-Si-Fe-Mg high thermal conductivity aluminum alloy also contains 0.0001-0.009% In by mass, 0.0001-0.005% Nb by mass, 0.001-0.005% Bi by mass, 0.0001-0.005% Ge by mass, 0.0001-0.005% Mo by mass, 0.0001-0.005% Ag by mass, 0.005-0.1% Sn by mass, 0.0001-0.005% Te by mass, and 0.001-0.008% Cd by mass.
8. A method for preparing the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy according to any one of claims 1 to 7, comprising the following steps: The aluminum source is subjected to a first heating treatment to obtain aluminum liquid; Adding Si, Fe, Cu, Mg, Sr, Zn, Co, Be, RE, and Ni to the aluminum liquid, performing a second heating treatment, and obtaining an alloy liquid; Refining and slagging the alloy liquid, and testing its composition and content; and After the composition and content are tested to be qualified, the alloy liquid after the refining treatment and the slag removal treatment is subjected to die casting treatment and aging treatment to obtain an Al-Si-Fe-Mg series high thermal conductivity aluminum alloy, wherein the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy contains 5-8% Si by mass, 0.4-0.8% Fe by mass, 0.001-0.05% Cu by mass, 0.11-0.4% Mg by mass, 0.005-0.04% Sr by mass, 0.001-0.05% Zn by mass, and 0.001-0.05% Zn by mass. 0.001-0.05% Ni, 0-0.1% Co, 0-0.01% Be, and 0.0001-0.1% RE by mass, the aging treatment includes a primary low-temperature aging treatment, a secondary low-temperature aging treatment, and a tertiary high-temperature aging treatment, wherein the temperature of the primary low-temperature aging treatment is -100°C to -200°C, and the time is 1h to 15h; the temperature of the secondary low-temperature aging treatment is 0°C to 70°C, and the time is 1h to 24h; the temperature of the tertiary high-temperature aging treatment is 280°C to 350°C, and the time is 0.05h to 15h.
9. The method for preparing the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy according to claim 8, characterized in that: Meet at least one of the following conditions: The aluminum source is at least one of original aluminum, aluminum ingot, and recycled aluminum; The preparation method of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy also includes the step of adding at least one of In, Nb, Bi, Ge, Mo, Ag, Sn, Te, and Cd to the aluminum liquid.
10. A heat dissipation structure, characterized in that: At least part of the heat dissipation structure is made of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy described in any one of claims 1-7 or the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy prepared by the preparation method of the Al-Si-Fe-Mg series high thermal conductivity aluminum alloy described in any one of claims 8-9.
Citation Information
Patent Citations
High-thermal-conductivity and high-strength cast aluminum alloy and preparation method thereof
CN114318080A
Hot-finishing strengthened die-casting aluminum alloy material for 5G mobile phone middle plate and preparation method of hot-finishing strengthened die-casting aluminum alloy material
CN114908273A
Aluminum alloy casting material with excellent thermal conductivity
JP2005298856A
Manufacturing method of aluminum alloy with high thermal conductivity
US11618935B1
Cited By
High-pressure casting aluminum alloy material, preparation method and application thereof in manufacturing radiator fins of frequency converter
CN122609865A